Analysis of information and communication needs in rural primary health care in developing countries. - Martinez, A. (IEEE Transactions on information technology in biomedicine)
This article presents three studies dealing with information and communication needs in rural primary health care from Peru and Nicaragua. Results show that primary health-care systems in rural areas of developing countries are very inefficient. Among the main reasons we found factors related to communication infrastructure, information sharing, and continuous training of health professionals. We conclude that telemedicine systems can improve this situation, but the lack of infrastructures, low income levels, and other conditions, impose strong limits to the introduction of new technologies. The main conclusion is that differences in needs and conditions between developing countries and industrialized ones force to use different solutions and approaches. This article presents some proposals on technology requirements and how to deal with the use of telemedicine in rural areas of developing countries. These proposals can be useful to all kind of actors (national public administrations, multilateral institutions, industry, academy, civil society, etc.) in order to promote really relevant and sustainable proposals in telemedicine for rural regions of developing countries.